2015
DOI: 10.1007/s00704-015-1472-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in indices of daily temperature and precipitations extremes in Morocco

Abstract: The purpose of this paper is to provide a summary of Morocco's climate extreme trends during the last four decades. Indices were computed based on a daily temperature and precipitation using a consistent approach recommended by the ETCCDI. Trends in these indices were calculated at 20 stations from 1970 to 2012. Twelve indices were considered to detect trends in temperature. A large number of stations have significant trends and confirm an increase in temperature, showing increased warming during spring and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 33 publications
7
43
1
Order By: Relevance
“…The Expert Team on Climate Change Detection and Indices (ETCCDI) has defined a set of 27 climate indices (Klein Tank and Lenderink, 2009;Zhang et al, 2011) that have been widely used for analysing changes in extremes (e.g. Frich et al, 2002;Kiktev et al, 2003;Alexander et al, 2006;Diaconescu et al, 2015Diaconescu et al, , 2016Filahi et al, 2016). In this study, we used the definitions proposed by Zhang et al (2011).…”
Section: Computation Of Climate Indices and Evaluation Of Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The Expert Team on Climate Change Detection and Indices (ETCCDI) has defined a set of 27 climate indices (Klein Tank and Lenderink, 2009;Zhang et al, 2011) that have been widely used for analysing changes in extremes (e.g. Frich et al, 2002;Kiktev et al, 2003;Alexander et al, 2006;Diaconescu et al, 2015Diaconescu et al, , 2016Filahi et al, 2016). In this study, we used the definitions proposed by Zhang et al (2011).…”
Section: Computation Of Climate Indices and Evaluation Of Methodologymentioning
confidence: 99%
“…Extremely wet days (mm) PRCPTOT Total wet-day precipitation (mm) indices were computed on an annual basis for 20 Moroccan stations: seven temperature-based indices and six precipitation-based indices (see Table 3). The trends from 1970 to 2010 of these climate indices computed with observations were previously analysed by Filahi et al (2016). Here these indices are compared with those simulated by the four RCMs presented in Table 2.…”
Section: Computation Of Climate Indices and Evaluation Of Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported most influential teleconnection patterns and their connections to surface air temperature (SAT) variability on regional, national, and global scales (e.g., [18][19][20][21]). A number of studies have particularly focused on links between changes in extreme temperatures and teleconnection patterns in different parts of the world (e.g., [22][23][24]). …”
Section: Introductionmentioning
confidence: 99%
“…A major challenge facing Morocco is the impact of climate change and the increased frequency of drought. Climate observations during the last four decades have shown that Morocco is experiencing major impacts from climate change through increased temperatures and decreased precipitations [4].…”
Section: Introductionmentioning
confidence: 99%